Inhibition mechanism of alpha-amylase, a diabetes target, by a steroidal pregnane and pregnane glycosides derived from Gongronema latifolium Benth - Ogunyemi, Oludare M.; Gyebi, Gideon A.; Saheed, Afolabi; Paul, Jesse; Nwaneri-Chidozie, Victoria; Olorundare, Olufunke; Adebayo, Joseph; Koketsu, Mamoru; Aljarba, Nada; Alkahtani, Saad; Batiha, Gaber El-Saber; Olaiya, Charles O. (Frontiers in Molecular Biosciences, 2022)
Alpha-amylase is widely exploited as a drug target for preventing postprandial hyperglycemia in diabetes and other metabolic diseases. Inhibition of this enzyme by plant-derived pregnanes is not fully understood. Herein, we employed in vitro, in silico and in vivo studies to provide further insights into the alpha-amylase inhibitory potential of selected pregnane-rich chromatographic fractions and four steroidal pregnanes phytochemicals (SPPs) viz: marsectohexol (P1) , 3-O-[6-deoxy-3-O-methyl-β-D-allopyranosyl-(1→14)-β-D-oleandropyranosyl]-11,12-di-O-tigloyl-17β-marsdenin (P2), 3-O-[6-deoxy-3-O-methyl-β-D-allopyranosyl-(1→4)-β-Doleandropyranosyl]-17β-marsdenin (P3) and 3-O-[6-deoxy-3-O-methyl-β-D-allopyranosyl-(1→4)-β-D-canaropyranosyl]-17β-marsdenin (P4) derived from Gongronema latifolium Benth. The results revealed that, the SPPs source pregnane-rich chromatographic fractions and the SPPs (P1-P4) exhibited inhibitory potential against porcine pancreatic alpha-amylase in vitro. Compounds P1 and P2 with IC50 values 10.01 µM and 12.10 µM respectively showed greater inhibitory potential than the reference acarbose (IC50 = 13.47µM). Molecular docking analysis suggests that the SPPs had strong binding affinity to porcine pancreatic alpha-amylase (PPA), human pancreatic alpha-amylase (HPA) and human salivary alpha-amylase (HSA); interacting with the key active site residues through an array of hydrophobic interactions and hydrogen bonds. The strong interactions of the SPPs with Glu233 and Asp300 residues may disrupt their roles in the acid-base catalytic mechanism and proper orientation of the polymeric substrates respectively. The interactions with HPA were maintained in a dynamic environment as indicated by the root mean square deviation, radius of gyration, surface accessible surface area and number of hydrogen bonds computed from the trajectories obtained from a 100 ns Molecular Dynamic simulation. Key loop regions of HPA that contribute to substrate binding exhibited flexibility and interaction potential towards the compounds as indicated by the Root Mean Square Fluctuation. Furthermore, P1 significantly reduced blood glucose level and area under the curve in albino rats which were orally challenged with starch. Therefore, Gongronema latifolium Benth. and its constituent SPPs may be exploited as inhibitors of pancreatic alpha-amylase towards as an oral policy for impeding postprandial blood glucose rise.